Factors regulating MAPK microdomain dynamics and the flow of spatial information in a spatially restricted neuron signaling network. - Tan, Sock Yee. (2012)
An integration of both the experimental data and computational modeling is essential to gain a mechanistic understanding of the complexity in the neuronal signaling network. In-silico approach is applied in this paper to validate the experimental data found from research papers in particular to exploring the neuronal signal information flow. Using Virtual Cell as a computational platform for modeling, it has been proven that factors such as negative regulator e.g. PDE4 together with shape geometry determine the downstream MAPK microdomain which is needed for memory formation. Using the same signaling network model, two more areas of ambiguity are being elucidated. The results have shown that there is a difference between spatial information flow and activity information flow within a signaling network. These two types of information are transmitted through two distinct pathways with the former involving PTP and the latter involving bRaf and MEK. It is also validated that dendritic spine density plays a part in synaptic plasticity. Beside these findings to validate the experimental results, new insights were also found which require further verification by experimental data. These include the interdependency of negative inhibition potential by negative regulators and their location in a neuron signaling pathway, the compensatory effect of increasing dendritic diameter as a result of increasing synaptic plasticity and the last will be that in order for synaptic plasticity to occur, some extent of inhibition on PDE4 is required. All these results provide a basis to pinpointing the exact cause of brain disorders such as Alzheimer’s disease and targeting these impairments without any other unnecessary complications with regard to the ambiguities of the fundamental.